2019
DOI: 10.3390/ma12182860
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Immersion and Type of Immersion Solution Distort the Outcome of Push-Out Bond Strength Testing Protocols

Abstract: This study aimed to investigate the influence of immersion duration and the type of immersion solution on the outcome of push-out bond strength (POBS) tests. Root canals of 120 straight single-rooted teeth were instrumented to a diameter of 1.5 mm and irrigated with 5 mL of 3% NaOCl. Four horizontal slices with a thickness of 1 mm were cut, representing the mid-portion of the root. The specimens (n = 480) were irrigated with 17% ethylenediaminetetraacetic acid(EDTA) for 60 seconds, then twice with distilled wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Hence, because of the different methodologies used in the various studies, a direct comparison with other POBS studies was difficult. Nevertheless, the POBS of AH Plus sealer was primarily better than that of BioRoot RCS, which was consistent with POBS after aging reported previously [ 14 16 , 28 ]. The improved bonding might be related to the covalent connections between the amino groups of the dentinal collagen and epoxy resin [ 29 ] so that the resulting polymer is heavily cross-linked and is thus rigid and strong [ 30 ] compared with the interaction of calcium silicates to dentin.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, because of the different methodologies used in the various studies, a direct comparison with other POBS studies was difficult. Nevertheless, the POBS of AH Plus sealer was primarily better than that of BioRoot RCS, which was consistent with POBS after aging reported previously [ 14 16 , 28 ]. The improved bonding might be related to the covalent connections between the amino groups of the dentinal collagen and epoxy resin [ 29 ] so that the resulting polymer is heavily cross-linked and is thus rigid and strong [ 30 ] compared with the interaction of calcium silicates to dentin.…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies evidence was found that the solubility, alkalizing potential, and bond strength of calcium silicate-based sealers depend on the immersion solution [ 4 , 15 ]. It was assumed that the precipitation of hydroxy apatite on the surface of calcium silicate-based materials after contact to phosphate concludes in a decrease of solubility [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even minor differences in the testing protocol might lead to a distortion of results, and duration of immersion and type of immersion solution displayed a significant impact on the push‐out bond strength (13). An alternative to obtaining clinically relevant results from push‐out bond strength tests is to use immersion solutions simulating body fluids as phosphate‐buffered saline (PBS) (13).…”
Section: Discussionmentioning
confidence: 99%
“…Donnermeyer et al (2019) evaluated the effect of the type and duration of immersion on the results of the push-out bond strength protocols and showed that the push-out bond strength of AH Plus was significantly higher than that of BioRoot RCS when comparing the same immersion solutions and immersion periods, and showed that the percentage of adhesive failure modes has increased while increasing sample storage time (13). Even minor differences in the testing protocol might lead to a distortion of results, and duration of immersion and type of immersion solution displayed a significant impact on the push-out bond strength (13). An alternative to obtaining clinically relevant results from push-out bond strength tests is to use immersion solutions simulating body fluids as phosphate-buffered saline (PBS) (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation